The Treatment of Aboriginal Children in Canada: A Violation of Human Rights Demanding Remedy - Filipetti, Clara (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2016)
This article examines two problems faced by the Canadian population: the current conditions of Aboriginal children and the lack of concrete course of action established to improve the dire conditions and lack of access to basic resources. This article proposes that a human rights framework can be utilized to address the disparities between Aboriginal and non-Aboriginal children in Canada. An integrated human rights framework acknowledges the complexity of the relationship between universal, natural and legal rights and provides a system of accountability to track the quality and success of the improvements made by the government of Canada. Due to the complex and systematic nature of the problem, a human rights framework provides a way to supplement the treaties and agreements that the government of Canada has often used as reasons for not taking responsibility. This paper concludes that an integrated human rights framework is an effective way to address the significant gaps between Aboriginal and non-Aboriginal children in terms of access and funding for social, health and educational services.